ETAR and protein kinase A pathway mediate ET-1 sensitization of TRPA1 channel: A molecular mechanism of ET-1-induced mechanical hyperalgesia. (May 2019) - Zheng, Xiaoli; Tai, Yan; He, Dongwei; Liu, Boyu; Wang, Chuan; Shao, Xiaomei; Jordt, Sven-Eric; Liu, Boyi
Endothelin-1 (ET-1) is a potent endogenous vasoconstrictor that has been widely known as a pain mediator involved in various pain states. Evidence indicates that ET-1 sensitizes transient receptor potential cation channel, subfamily A, member 1 (TRPA1) in vivo . But the molecular mechanisms still remain unknown. We aim to explore whether ET-1 sensitizes TRPA1 in primary sensory neurons and the molecular mechanisms. Ca 2+ imaging, immunostaining, electrophysiology, animal behavioral assay combined with pharmacological experiments were performed. ET-1 sensitized TRPA1-mediated Ca 2+ responses in human embryonic kidney (HEK)293 cells as well as in cultured native mouse dorsal root ganglion (DRG) neurons. ET-1 also sensitized TRPA1 channel currents. ET-1 sensitized TRPA1 activated by endogenous agonist H2 O2 . ETA receptor (ETA R) colocalized with TRPA1 in DRG neurons. ET-1-induced TRPA1 sensitization in vivo was mediated via ETA R and protein kinase A (PKA) pathway in HEK293 cells and DRG neurons. Pharmacological blocking of ETA R, PKA, and TRPA1 significantly attenuated ET-1-induced mechanical hyperalgesia in mice. Our results suggest that TRPA1 acts as a molecular target for ET-1, and sensitization of TRPA1 through ETA R–PKA pathway contributes to ET-1-induced mechanical hyperalgesia. Pharmacological targeting of TRPA1 and ETA R-PKA pathway may provide effective strategies to alleviate pain conditions associated with ET-1.